2018
DOI: 10.1177/1071100718803131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following Minimally Invasive Dorsal Cheilectomy for Hallux Rigidus

Abstract: Background: Following failure of conservative treatment, a dorsal cheilectomy can be performed for patients in early stages of hallux rigidus by a traditional open approach or by a minimally invasive technique. We report our clinical outcomes following minimally invasive dorsal cheilectomy (MIDC). Methods: Eighty-nine patients (98 feet) with symptomatic hallux rigidus treated between 2011 and 2016 were included in this study. The average age was 54 years. Manchester-Oxford Foot Questionnaire (MOxFQ) scores and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…We found only a few studies that describe the timing of the revision surgery. One of these studies, which described the long-term results of minimally invasive dorsal cheilectomy, 21 similarly found that most of the failures were within the first 2 years postsurgery. Another study reported a 4.9% failure rate, documented as revisions in mid- to long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We found only a few studies that describe the timing of the revision surgery. One of these studies, which described the long-term results of minimally invasive dorsal cheilectomy, 21 similarly found that most of the failures were within the first 2 years postsurgery. Another study reported a 4.9% failure rate, documented as revisions in mid- to long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,13 In the present study, none of the patients undergoing open dorsal cheilectomy procedures required further surgery for dorsal impingement pain. Correspondingly, with MIS dorsal cheilectomy, using the technique advocated by Redfern et al, 18 the sole study in the literature with a relatively large number of patients 23 identified a failure to relieve symptoms in 12% of cases, with 4% requiring further dorsal cheilectomy surgery for dorsal impingement pain. These results from Teoh et al 23 reflect the findings of the present study, in which 3.8% (5/133) of patients had to undergo a further dorsal cheilectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is acknowledged as a “learning curve.” Within the literature, there are no references to a learning curve for performing an open dorsal cheilectomy, but it is readily accepted as being a straightforward operative technique. In the study by Teoh et al, 23 the technique for MIS dorsal cheilectomy appears to be subject to a learning curve. This was assessed by 2 endpoints: (1) attributing 42% of the cases requiring reoperation to poor technique and (2) observing a decreasing intraoperative fluoroscopic screening time as the case series progressed chronologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sala cirúrgica estava equipada com um intensificador de imagem, um motor elétrico e os instrumentais necessários para a cirurgia percutânea (raspas, fresas, lâminas) (14,15) . O primeiro passo cirúrgico foi a queilectomia percutânea dos osteófitos dorsal e dorso-lateral (19) presentes na cabeça do primeiro metatatarsal (Figura 1), através de uma incisão com cerca de 1cm. Os detritos ósseos foram retirados pela compressão do hálux e a saída dos mesmos pela incisão prévia, além da limpeza com soro fisiológico em uma seringa inserida no portal (14,15) .…”
Section: Técnica Cirúrgicaunclassified